Corporate Social Responsibility in Nigeria: Realities, Modalities and Possibilities - OYEWUNMI, Adebukola E.; OYEWUNMI, Olabode A. (Journal of Advanced Research in Law and Economics, 2018)
This conceptual paper provides a non-revisionist but contextual perspective on the largely controversial issue of corporate social responsibility. It expounds the dimensions of CSR by leveraging on specific global benchmarks whilst highlighting gaps applicable to Nigeria’s business environment. In furtherance of this objective, the essence of the global oil economy is noted, conceptualizations are proffered and contextual issues are discussed. The paper argues that a flexible and innovative model is plausible as a platform to elevate the essence of CSR on multiple levels. It emphasizes the importance of harmonizing the political, business, environmental and legal aspects of CSR to promote corporate sustainability, broad based economic development and community wellbeing.